2018
DOI: 10.1097/icl.0000000000000399
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Characteristics and Prescribing Patterns of Scleral Lens Fitters: The SCOPE Study

Abstract: Eye care providers of all ages are fitting scleral lenses. The number of individuals who fit this lens modality has increased during the past decade. Scleral lenses are being fit by providers in a wide range of practice settings. Most scleral lenses are prescribed for corneal irregularity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 38 publications
0
59
0
3
Order By: Relevance
“…This study may not accurately represent scleral lens outcomes worldwide, as data was collected using an English language survey. However, a larger percentage of responses in this study were from international prescribers (40%) compared to the original SCOPE study [18], in which 23% of prescribers reported residency outside of the United States. Lack of standardized methods of measuring visual acuity or assessing corneal staining may also represent a weakness in this retrospective study.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…This study may not accurately represent scleral lens outcomes worldwide, as data was collected using an English language survey. However, a larger percentage of responses in this study were from international prescribers (40%) compared to the original SCOPE study [18], in which 23% of prescribers reported residency outside of the United States. Lack of standardized methods of measuring visual acuity or assessing corneal staining may also represent a weakness in this retrospective study.…”
Section: Discussionmentioning
confidence: 56%
“…The results of these single-center studies may not be generalizable to other lens designs, practice modalities and fitting philosophies. Results of a worldwide survey of general scleral lens prescription and management strategies were recently reported [17][18][19]. While these studies provided a better understanding of the indications for scleral lens use along with T information on lens designs being prescribed, care products recommended, and demographics of scleral lens prescribers, they do not offer insight into outcomes of scleral lens wear.…”
Section: Introductionmentioning
confidence: 99%
“…The prescription of scleral contact lenses as well as the number of practitioners who fit scleral contact lenses has notably increased over the last few years [1][2][3]. Scleral lens prescription and management is no longer limited to highly specialized care centres [4].…”
Section: Introductionmentioning
confidence: 99%
“…Although modern rigid gas permeable scleral contact lenses were first described in 1983 [1], widespread interest in scleral lenses has markedly increased only during the last decade [2,3]. Many of the practitioners fitting scleral lenses are recent graduates [4]. There is limited consensus on the most appropriate strategies for fitting these lenses, many of which are prescribed for diseased eyes.…”
Section: Introductionmentioning
confidence: 99%